46, XY Disorder of Sex Development Caused by 17α-Hydroxylase/17, 20-Lyase Deficiency due to Homozygous Mutation of CYP17A1 Gene: Consequences of Late Diagnosis. (24th April 2018) - Papi, Giampaolo; Paragliola, Rosa Maria; Concolino, Paola; Di Donato, Carlo; Pontecorvi, Alfredo; Corsello, Salvatore Maria
Abstract : Context. Congenital adrenal hyperplasia (CAH) is an autosomal recessive disease due to specific enzyme deficiencies in the adrenal steroidogenesis pathway. Case Description. A 40-year-old Chinese woman was referred to the Endocrine Unit for the work-up of a syndrome characterized by long-lasting and multidrug resistant high blood pressure, severe hypokalemia with metabolic alkalosis, and primary amenorrhea. The patient presented with sexual infantilism, lack of breast development, absence of axillary and pubic hair, tall stature, and slenderness. CT scan revealed enlarged adrenal glands bilaterally and the absence of the uterus, the ovaries, and the Fallopian tubes. Furthermore, diffuse osteopenia and osteoporosis and incomplete ossification of the growth plate cartilages were demonstrated. Chromosomal analysis showed a normal male 46, XY, karyotype, and on molecular analysis of the CYP17A1 gene she resulted homozygous for the g.4869T>A; g.4871delC (p.Y329Kfs?) mutation in exon 6. Hydrocortisone and ethinyl-estradiol supplementation therapy led to incomplete withdrawal of antihypertensive drug and breast development progression to Tanner stage B2 and slight height increase, respectively. Conclusions. We describe a late-discovered case of CAH with 46, XY disorder of sex development. Deficiency of 17 α -hydroxylase/17, 20-lyase due to a homozygous CYP17A1 gene mutation was the underlying cause. Laboratory, imaging, and genetic features are herein reported and discussed.